A dual‐input DC‐DC structure with high voltage gain suggested for hybrid energy systems. Issue 10 (27th May 2021) - Pourjafar, Saeed; Shayeghi, Hossein; Sedaghat, Farzad; SeyedShenava, SeyedJalal
Abstract: This paper proposes a non‐isolated dual‐input DC‐DC converter with high voltage rate recommended for hybrid renewable sources/energy storage applications. The suggested converter can transfer power between two different sources in different conditions and can also provide the required energy of the load at the desired voltage level. The output voltage can be improved by utilizing magnetic coupling and a super voltage lift circuit (SLVC). The maximum voltage through the semiconductors can be decreased by using the SLVC technique. In addition, the suggested converter can draw continuous input current from two input DC supplies that lead to an increase in the lifetime of the input supplies. Besides, there is soft‐switching capability throughout the diodes, which leads to alleviate the reverse recovery losses and improve efficiency. To prove the performance of the suggested topology, the technical survey and mathematical analysis are carried out in the literature. A laboratory prototype with 20 and 12 V input DC supplies is prepared in this work to demonstrate the correctness of the recommenced converter operation.